KARAKTERISTIK AMILOGRAFI TEPUNG SORGUM FERMENTASI DAN APLIKASINYA PADA PRODUK CAKE DAN COOKIES SORGUM - Raden Haryo Bimo Setiarto; Nunuk Widhyastuti; Iwan Saskiawan (Jurnal Dinamika Penelitian Industri, 2017)
This study aims to investigate the characteristics of fermented sorghum flour amylograph and organoleptic test of the product cake and cookies from fermented sorghum flour. Production of sorghum flour was made with four variations of treatments, ie: control (without fermentation), solid fermentation, liquid fermentation, mixture fermentation (solid and liquid). Amylograph profile analyzes the four samples of sorghum flour was conducted with Viscograph Brabender. In the manufacture of cookies and cake, wheat flour can be substituted with fermented sorghum flour on percentage (0%, 25%, 50%, 75%, 100%). Organoleptic test of the product cake and cookies sorghum were calculated using hedonic test. The results of amylograph analysis indicated that sorghum flour with liquid fermentation treatment has the best profile of gelatinization because it had resistance, high stability about heating and it also had a good setback viscosity. Overall, cookies and cake was made from mixture of sorghum flour and wheat flour in the ratio 1 : 1 (substitution of wheat flour 50%) were well received by the panelists.